Performance enhancing drug abuse and cardiovascular risk in athletes: implications for the clinician. (24th October 2012) - Angell, Peter J; Chester, Neil; Sculthorpe, Nick; Whyte, Greg; George, Keith; Somauroo, John
Abstract : The use of performance-enhancing and social drugs by athletes raises a number of ethical and health concerns. The World Anti-Doping Agency was constituted to address both of these issues as well as publishing a list of, and testing for, banned substances in athletes. Despite continuing methodological developments to detect drug use and associated punishments for positive dope tests, there are still many athletes who choose to use performance and image enhancing drugs. Of primary concern to this review are the health consequences of drug use by athletes. For such a large topic we must put in place delimitations. Specifically, we will address current knowledge, controversies and emerging evidence in relation to cardiovascular (CV) health of athletes taking drugs. Further, we delimit our discussion to the CV consequences of anabolic steroids and stimulant (including amphetamines and cocaine) use. These drugs are reported in the majority of adverse findings in athlete drug screenings and thus are more likely to be relevant to the healthcare professionals responsible for the well-being of athletes. In detailing CV health issues related to anabolic steroid and stimulant abuse by athletes we critique current research evidence, present exemplar case studies and suggest important avenues for on-going research. Specifically we prompt the need for awareness of clinical staff when assessing the potential CV consequences of drug use in athletes.